2020
DOI: 10.13057/biodiv/d220112
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: Characterization and nutrient analysis of seed of local cowpea (Vigna unguiculata) varieties from Southwest Maluku, Indonesia

Abstract: Abstract. Karuwal RL, Suharsono, Tjahjoleksono A, Hanif N. 2021. Short Communication: Characterization and nutrient analysis of seed of local cowpea (Vigna unguiculata) varieties from Southwest Maluku, Indonesia. Biodiversitas 21: 85-91. Cowpea (Vigna unguiculata (L.) Walp.) is a legume species that have many local varieties across regions in Indonesia, including in Southwest Maluku District. It has been utilized by the community as raw materials, but mainly for food sources of self-consumption. While there ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Significant statistical differences were recorded for seven cowpea landraces from Indonesia that were compared with three commercial varieties. Among them, landrace “KM7” presented high lipid and protein content, and “KM1” presented high carbohydrate and folic acid content [ 361 ]. A local variety “GH3684” presented lower carbohydrate seed content but higher fiber content compared to six advanced and parental lines [ 362 ].…”
Section: Cowpea Plant Genetic Resources For Main Productivity Constra...mentioning
confidence: 99%
“…Significant statistical differences were recorded for seven cowpea landraces from Indonesia that were compared with three commercial varieties. Among them, landrace “KM7” presented high lipid and protein content, and “KM1” presented high carbohydrate and folic acid content [ 361 ]. A local variety “GH3684” presented lower carbohydrate seed content but higher fiber content compared to six advanced and parental lines [ 362 ].…”
Section: Cowpea Plant Genetic Resources For Main Productivity Constra...mentioning
confidence: 99%
“…Plant morphological variation typically provides feedback for the evolving climatic circumstances and indicates adaptive evolution, even though genetic variation is more precise in assessing variety. This helps breeders in taking into account both the innate genetic makeup and environmental influences involved in crop improvement (Karuwal et al, 2021). Researches then study genetic variations and diversity by observing phenotypic expressions of the plant through the use of morphological characters.…”
Section: Introductionmentioning
confidence: 99%
“…The practical applications of these variations are also tied to their phenotypic expressions. More recently, Karuwal et al (2021), examined the seed of regional cowpea cultivars from Southwest Maluku, Indonesia for their morphological and nutritional characters. Their findings demonstrated that the samples varied significantly.…”
Section: Introductionmentioning
confidence: 99%